Carbon footprint assessment at Universiti Teknologi Mara Seri Iskandar Campus, Malaysia / ... [et al.] - Nor Izana, Mohd Shobri; Wan Noor Anira, Wan Ali@Yaacob; Norizan, Mt Akhir; Siti Rasidah, Md Sakip (Universiti Teknologi MARA, Perak, 2017)
The purpose of this study is to assess the carbon footprint emission at UiTM Perak, Seri Iskandar Campus. The assessment focuses on electrical power and transportation usage. Questionnaires were distributed to the staffs and students to survey their transportation usage in the year 2014 while for electrical consumption, the study used total energy consumed in the year 2014. Data was calculating with the formula by Green House Gas Protocol. Total carbon footprint produced by UiTM Perak, Seri Iskandar Campus in the year 2014 is 11842.09 MTCO . The result of the study is hoped to provide strategies for the university to reduce the carbon footprint emission.